An Approach to Enhancing Local Assets for green area protection — a Case Study on Song Khlong, Chachoengsao Thailand - et. al., Wanpen Charoentrakulpeeti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Green areas are continually being decreased due to urbanization although it has been controlled by city planning law. This article aims to propose strategies to maintain green areas in the Song Khlong area based on a value-added planning approach. An inventory of the existing communities' fund and green spaces was established as communities’ database. Subsequently, a map of these data was created with community participation. Thereafter, strategies for either reducing the running costs or generating income were taken into consideration. It is possible to promote ecotourism in the Song Khlong areas as the major activities during weekends of people living and working around Song Khlong are shopping (48%), going to the temple (20%), going to the beach nearby such as Bang Saen beach (11%), going to the floating market (9%), and others (9%). Therefore, three projects were proposed, including (1) aesthetic improvement along the RiebKhlong road, (2) development of the WatTrisaranakom floating market, and (3) conservative tourism development in the mangrove forests of the Song Khlong village. All three projects support each other: activities on day trips can mostly be at the floating market, with going for a stroll could be at the nature-learning trails and staying for overnight at homestay. This is not just nature learning; it can simultaneously be a learning of community lifestyle with sustainably maintaining green areas